The Hevea brasiliensis AP2/ERF superfamily: from ethylene signalling to latex harvesting and physiological disease response - Riza Arief PUTRANTO; Pascal MONTORO (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2016)
Ethylene is a hormone known for its involvement in the process of latex harvesting in Hevea brasiliensis. It facilitates latex flow by activation of endogenous metabolism in the anastomosed latex cells called laticifers. In regard to its ambivalent role, ethylene is both favourable to the latex production and unfavourable, to a certain level, to the apparition of a physiological disease termed as tapping panel dryness (TPD). Comprehensive researches have been carried out to reveal the molecular actors in ethylene biosynthesis and signalling pathways in Hevea brasiliensis. One of the most important superfamily implicated as the last transcription factor known in plant ethylene signalling is the APETALA2/ETHYLENE RESPONSE FACTOR (AP2/ERF). Currently, 114 unique sequences related to the Hevea AP2/ERF gene superfamily have been identified and characterized. Specific characterizations under the condition of harvesting stress and the occurrence of TPD have identified 36 gene expression markers (GEMs). Eighteen of these GEMs were predicted as ortholog with 19 Arabidopsis AP2/ERF genes. The characterization was mainly focused on transcriptional regulation, whilst potential post-transcriptional and post-translational regulations of HbAP2/ERF genes were formerly predicted. Three HbERF groups (HbERF-VII, HbERF-VIII and HbERF-IX) were hypothesized to have an important role in Hevea tolerance during latex production as they highly accumulated in laticifers and in response to multiple abiotic stresses. Further functional analysis of several key genes is suggested in order to fully understand the regulation of HbAP2/ERFs. Finally, the molecular markers for future Hevea breeding could be possibly developed from this superfamily.